2021
DOI: 10.3389/fmars.2021.759744
|View full text |Cite
|
Sign up to set email alerts
|

Endosymbiont Communities in Pachyseris speciosa Highlight Geographical and Methodological Variations

Abstract: Reef-building corals live in symbiosis with the phototrophic dinoflagellate family Symbiodiniaceae, which comprises diverse genera such as Cladocopium and Durusdinium. Pachyseris speciosa, a widely distributed Indo-Pacific coral found in a variety of reef habitats, is known to be associated with these two Symbiodiniaceae genera, but little is known about the biogeographic variability of the endosymbiont communities across the region. In this study, the diversity and dominance patterns of Symbiodiniaceae at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
1
0
0
Order By: Relevance
“…For instance, Rubin et al 54 found that P. strigosa in the Port of Miami primarily hosted more heat-tolerant zooxanthellae in the genus Durusdinium vs. those at our natural control site, Emerald Reef, which primarily hosted Breviolum . Similar associations with stress-tolerant symbionts have been observed in urbanized habitats in Singapore 60 , 61 , as well as in environmentally-variable lagoon environments 62 . Prokaryotic communities also tend to reflect the environment in which the coral resides, where corals in marginal habitats can host divergent mucus-associated bacteria 63 .…”
Section: Discussionsupporting
confidence: 77%
“…For instance, Rubin et al 54 found that P. strigosa in the Port of Miami primarily hosted more heat-tolerant zooxanthellae in the genus Durusdinium vs. those at our natural control site, Emerald Reef, which primarily hosted Breviolum . Similar associations with stress-tolerant symbionts have been observed in urbanized habitats in Singapore 60 , 61 , as well as in environmentally-variable lagoon environments 62 . Prokaryotic communities also tend to reflect the environment in which the coral resides, where corals in marginal habitats can host divergent mucus-associated bacteria 63 .…”
Section: Discussionsupporting
confidence: 77%
“…This was unexpected since numerous studies suggest anything smaller than 1 mm is unlikely to show biogeographic patterns [71], and that for microscopic organisms dispersal is assumed to be rarely, if ever, limited by geographical barriers [72]. However, work in Southeast Asia examining mangrove [73,74], seagrass [66,75], and coral associated microbiota [76][77][78] shows that microbial biogeographic structure can exist over comparatively small spatial scales (< 6 km in some instances). Further supporting these observations, work by Jenkins et al, [79] similarly showed that a smaller size does not lead to further dispersal and a more cosmopolitan distribution.…”
Section: Traits Of Differentially Abundant Taxamentioning
confidence: 99%
“…For instance, the proportion of Durusdinium in Orbicella faveolata increased differently in response to short-and long-term heat stress exposure, depending on the severity of the disturbance (Cunning et al, 2015). Similarly, several studies have revealed that a largescale spread of heat-stress tolerant symbionts is correlated with corals living in warmer oceans (Pettaya et al, 2015;Jain et al, 2021); this rapid shift in Symbiodiniaceae can potentially enhance the corals' survival in the face of unstable environmental conditions. Nevertheless, this mechanism may not be sufficient to ensure the survival of all corals under the predicted conditions of future climate change, which can vary depending on the severity of stress, geographic locations, coral taxa, etc.…”
Section: Introductionmentioning
confidence: 99%